2018
DOI: 10.1371/journal.pone.0202054
|View full text |Cite
|
Sign up to set email alerts
|

Enteric virome of Ethiopian children participating in a clean water intervention trial

Abstract: BackgroundThe enteric viruses shed by different populations can be influenced by multiple factors including access to clean drinking water. We describe here the eukaryotic viral genomes in the feces of Ethiopian children participating in a clean water intervention trial.Methodology/principal findingsFecal samples from 269 children with a mean age of 2.7 years were collected from 14 villages in the Amhara region of Ethiopia, half of which received a new hand-dug water well. Feces from these villages were then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
35
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 47 publications
13
35
4
Order By: Relevance
“…This epidemiological information on the genetic diversity of EV contributes to the growing knowledge of genotypes circulating in Ethiopia. Most of the genotypes detected in this study were reported from previous studies in Ethiopia and other sub‐Saharan African countries 19‐24 . The frequent detection of EV‐B and EV‐C in this study is comparable with a previous study in Ethiopia in 2016 19 .…”
Section: Discussionsupporting
confidence: 89%
“…This epidemiological information on the genetic diversity of EV contributes to the growing knowledge of genotypes circulating in Ethiopia. Most of the genotypes detected in this study were reported from previous studies in Ethiopia and other sub‐Saharan African countries 19‐24 . The frequent detection of EV‐B and EV‐C in this study is comparable with a previous study in Ethiopia in 2016 19 .…”
Section: Discussionsupporting
confidence: 89%
“…There are two possible reasons for limited worldwide HPeV15 detection: (i) silent transmission due to HPeV underdiagnosis explained by the lack of HPeV routine testing in clinical settings and lack of awareness among clinicians 1 , or (ii) localized geographical circulation of the virus in parts of Africa and Asia. However, in Africa, none of the studies conducted between 2002 and 2016 for HPeV detection in stool samples detected HPeV15 strains, neither in healthy nor in children with gastrointestinal symptoms [23][24][25][26] , except for one study from Ghanaian children in 2007-2008 11 . Nevertheless, these studies highlight the high genetic diversity of HPeVs in Africa, which include rare types like HPeV16, HPeV17 or the new type HPeV18 11,23,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in Africa, none of the studies conducted between 2002 and 2016 for HPeV detection in stool samples detected HPeV15 strains, neither in healthy nor in children with gastrointestinal symptoms [23][24][25][26] , except for one study from Ghanaian children in 2007-2008 11 . Nevertheless, these studies highlight the high genetic diversity of HPeVs in Africa, which include rare types like HPeV16, HPeV17 or the new type HPeV18 11,23,25,26 . The studies that detected HPeVs in respiratory samples in African countries (Tunisia, Kenya and Gabon) did not perform type identification and therefore it is not possible to know whether type 15 was detected in these samples [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E7 genome is most similar to that of isolate Env_2016_Sep_E-7a (GenBank accession number MG451805 ), another E7 recovered from sewage in the United Kingdom in 2016, but has been suggested to be of sub-Saharan African origin ( 9 ). The E19 genome, on the other hand, is most similar to that of isolate ETH_P3/E19_2016 ( MF990292 ), an E19 recovered in April 2016 from the stool of a child in Ethiopia ( 10 ). Though EV-B genomic ends have been well characterized and the primers used in this study are based on conserved sequences ( 3 8 ), considering that the primers were used for amplification, the ends of the genomes might be of primer origin.…”
Section: Announcementmentioning
confidence: 96%